Design and Analysis of Microstrip Patch Antenna Using Different Feeding Techniques - Singh, Jaget; Sohi, BS (International Journal of Computer Sciences and Engineering, 2025)
In this paper a microstrip patch antenna is designed using the different feeding techniques. Selection of feeding technique is very crucial point for an antenna design. If proper technique is not used for feeding the antenna, more power will be reflected back and reduce the power available for radiations and also affect the performance parameters like gain, return, loss and directivity of antenna. For the current paper the microstrip antenna is designed using the microstrip and coaxial feeding line. The results for both the designs are compared and analyzed. The return loss and bandwidth of probe feed antenna is -40.8 dB and 112 MHz which is higher than that transmission line feed antenna which is -27 dB and 88 MHz respectively. The gain is 7 dB and 5.74 dB for probe feed and transmission line feeding antenna respectively. The return loss, gain and bandwidth of antenna with probe feed are higher than that of transmission line feeding. But for a planar structure, probe feed is technique lose the planar characteristics of antenna.